Cutting Capability Assessment of Highly Porous CBN Wheels by Microrelief of Plane Parts from 06Cr14Ni6Cu2MoWÐ¢i-Sh Steel Using Artificial Intelligence System - Yakov Iosifovich Soler; Nguyen Manh Tiem; Nguyen Van Le (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
The abrasive tools are the weakest element in the grinding process system, to which great attention is being paid by scientific and industrial collectives. Eleven highly porous wheels (HPWs) were tested: CBN30 (B76, B107, B126, B151) 100 OVK27-ÐšF40; CBN30 B107 100 OVKC10-ÐšF40; CBN30 B126 100(M, L) VK27- (ÐšF25, ÐšF40); LKV50 (B107, B126) 100 (M, O) VK27-ÐšF40. Assessment of the surface topography was carried out by roughness parameters Ra, Rmax, and Sm(GOST 25472-82), which were considered random variables with their position and dispersion measures. Two artificial intelligence systems